Microsurgical reconstruction of Stensen's duct using autologous vein graft and venous coupler after ablative head and neck surgery. Issue 5 (13th April 2021) - Irawati, Nina; Clark, Jonathan R
Abstract : We describe our technique which is simple and feasible to reconstruct the parotid duct orifice after cancer ablative surgery.